Learning on the Ground: Ecology, Engagement, and Embodiment - Ayres, Jennifer R. (Teaching theology and religion, 2014)
If theological education is to prepare religious leaders who will respond faithfully and capably to ecological challenges, what models of teaching and learning will best equip them for this work? In conversation with environmental education theory and examples from diverse learning contexts, this paper proposes a model of “learning on the ground” which is characterized by engaged and embodied pedagogy through participation in earth-honoring social practices. See a companion essay in this issue of the journal (Kevin J. O'Brien, “Balancing Critique and Commitment”) and a response to both these essays (Forrest Clingerman, “Pedagogy as a Field Guide to the Ecology of the Classroom”) also published in this issue of the journal.